2011
DOI: 10.1096/fj.11-185017
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A 4 and benzo‐lipoxin A 4 attenuate experimental renal fibrosis

Abstract: Unresolved inflammation underlies the development of fibrosis and organ failure. Here, we investigate the potential of the proresolving eicosanoid lipoxinA₄ (LXA₄) and its synthetic analog benzo-LXA₄ to prophylactically modulate fibrotic and inflammatory responses in a model of early renal fibrosis, unilateral ureteric obstruction (UUO). Male Wistar rats (Animalia, Chordata, Rattus norvegicus) were injected intravenously with vehicle (0.1% ethanol), LXA₄ (45 μg/250-g rat), or benzo-LXA₄ (15 μg/250-g rat) 15 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 66 publications
3
91
0
1
Order By: Relevance
“…5 Here we report that LXA 4 analog is associated with increased renal let-7c expression in vivo ( Figure 2E). …”
Section: Lxa 4 Attenuates Tgf-b1 Responses Of Renal Epitheliamentioning
confidence: 58%
See 2 more Smart Citations
“…5 Here we report that LXA 4 analog is associated with increased renal let-7c expression in vivo ( Figure 2E). …”
Section: Lxa 4 Attenuates Tgf-b1 Responses Of Renal Epitheliamentioning
confidence: 58%
“…We previously demonstrated that LXA 4 attenuates collagen deposition in an animal model for renal fibrosis, and attenuates the upregulation of let-7c target COL1A2. 5 Minimal free energy calculations for let-7c pairing with 39 UTR recognition sites indicated the formation of stable hybrid structures between let-7c and COL1A1 (DG = 220.8 kcal/mol ). TGF-b1 stimulation of HK-2 cells (10 ng/ml; 24 hours) resulted in significant upregulation of COL1A1, COL1A2, and THBS1 gene expression, and transfection with let-7c miRNA mimic suppressed TGFb1-mediated upregulation of these genes ( Figure 6, B, D, and F).…”
Section: Lxa 4 Attenuates Tgf-b1 Responses Of Renal Epitheliamentioning
confidence: 96%
See 1 more Smart Citation
“…Several molecules were proposed to be involved in the profibrotic switch of fibroblasts (or pericytes) during renal fibrosis, including the Wnt signaling pathway (e.g., Wnt4, LRP-6, and DKK-1) (183,184), oxidative stress and NADPH oxidase (39,88,185), integrins including aV integrin (186), Rheb/mTORC1 signaling (187) as well as lipid mediators, including prostaglandins and their receptors like EP4 (188,189), prostacyclins (190), or lipoxins (191,192).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…Previous studies have shown that LXA4 can attenuate airway inflammation following lipopolysaccharide (LPS)-induced lung injury in mice (6), reduce systemic inflammation and improve Lipoxin A4 exerts protective effects against experimental acute liver failure by inhibiting the NF-κB pathway survival rates in a rat model of sepsis (7), suppress inflammation-induced mechanical hypersensitivity in rats (8), and inhibit pulmonary and renal fibrosis in animal models (9,10). In addition, the levels of LXA4 are decreased in patients with asthma (11).…”
Section: Introductionmentioning
confidence: 99%